Spiritual nurturing of children living in the context of poverty, with specific reference to the role of the Christian children's worker. - Mathewson, Susanna Elizabeth (Stellenbosch : Stellenbosch University, 2011)
Thesis (MTh)--Stellenbosch University, 2011.